Technical study on conservation and restoration of Niavaran Palace’s embroidered Pateh - Barkeshli, Mandana; Janpourtaher, Mina (2014)
A historical and scientific analysis was carried out on a historical textile from Sahebgharanieh Niavaran Palace’s collection. The examination shows that the sample under study is embroidered in Pateh technique. It belongs to Iran, dated around late 18th Century, from Qajar dynasty period. To conserve and restore the textile sample under study, the material technology on its fiber, weave and motif were identified. The scientific analysis shows that the fiber is made of wool, with Twill weave technique, decorated with embroidered fiber made of silk. With the help of SEM-EDX method of analysis it is detected that the fabric contains a great value of silver and gilt scythes using metallic thread with delicate silk yarns. Motifs used in the fabric are of paisley leaf with decorative motifs of plant and animal embroidered beautifully. The Fabric was graphically documented by microscopic and macroscopic methods and its degree of damage was assessed. This leads to the implementation of conservation, restoration and display techniques, which was carried out in the textile division of Sahebgharanieh Niavaran Palace Museum. It will be discussed in detail later in the paper. The paper employs scientific analysis and SEM-EDX method to analyze the historical textile. The major aim and objective of the study is to know the materials and contents from which the textile is made in order to know the best restoration and preservation method that may be applied in preserving and conserving the historical textile and the likes of it.